EXPLORING MEDICAL DATABASE AND DATA MINING IN THE AGE OF BIG DATA (International Journal of Food and Nutritional Sciences, 2022)
Data mining is used to extract meaning from huge databases. Big Data includes the expression, preparation, mining, and analysis of data. Databases are essential to this revolutionary technique of data handling. The branch of computer science concerned with database administration and comprehension is known as database technology. Database analysis necessitates investigation into both the theory and practice of data storage, administration, design, and application. Our seminars on databases and data extraction benefited many medical experts.